2007
DOI: 10.1021/tx700231a
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopentenone Prostaglandin, 15-Deoxy-Δ12,14-PGJ2, Is Metabolized by HepG2 Cells via Conjugation with Glutathione

Abstract: 15-deoxy-Delta12,14-prostaglandin J2 (15-d-PGJ2) is a dehydration product of PGD2. This compound possesses a highly reactive polyunsaturated carbonyl moiety that is a substrate for Michael addition with thiol-containing biomolecules such as glutathione and cysteine residues on proteins. By reacting with glutathione and proteins, 15-d-PGJ2 is believed to exert potent biological activity. Despite the large number of publications that have ascribed bioactivity to this molecule, it is not known to what extent 15-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 24 publications
6
25
0
Order By: Relevance
“…The unsaturated carbonyl groups of cyclopentenone PGs rapidly react with thiol-containing proteins and peptides, and measurements of 15-d-PGJ 2 (or other cyclopentenone PGs) in vivo underestimates true concentrations. Thus, 15-d-PGJ2 is detectable in vivo primarily as a Michael conjugate to gluthatione (42). The same consideration applies to the measurement of 8-iso-PGA 2 levels at sites of inflammation or tissue injury (22).…”
Section: Discussionmentioning
confidence: 99%
“…The unsaturated carbonyl groups of cyclopentenone PGs rapidly react with thiol-containing proteins and peptides, and measurements of 15-d-PGJ 2 (or other cyclopentenone PGs) in vivo underestimates true concentrations. Thus, 15-d-PGJ2 is detectable in vivo primarily as a Michael conjugate to gluthatione (42). The same consideration applies to the measurement of 8-iso-PGA 2 levels at sites of inflammation or tissue injury (22).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that glutathione transferase (GST)- pi in livers of IL-4 −/− mice may catalyze the conjugation of GSH with NAPQI more rapidly than in livers of WT mice (42). GSH may also form more conjugates with other electrophiles in livers of IL-4 −/− mice including those with 4-hydroxy-2-nonenal (43), 15-deoxy- 12,14 -PGJ2 (44), and perhaps oxidized proteins forming S-glutathionylated protein adducts (45). …”
Section: Discussionmentioning
confidence: 99%
“…CID experiments confi rmed pounds, we sought to determine whether deoxy-J 2 -IsoPs would adduct GSH, an abundant cellular thiol, in the presence of GST. We have previously shown that 15-d-PGJ 2 and other cyclopentenone eicosanoids readily adduct GSH in the presence of GST in vitro (26)(27)(28)(29)(30). In the present study, we incubated deoxy-J 2 -IsoPs generated from the nonenzymatic oxidation of AA in vitro with GSH in the presence of GST.…”
Section: Adduction Of Deoxy-j 2 -Isops With Gsh In Vitromentioning
confidence: 99%
“…This may be due to the rapid reactivity of 15-d-PGJ 2 . Previous studies have indicated that cyclopentenone eicosanoids rapidly undergo conjugation with GSH in vitro and in vivo (26)(27)(28)(29)(30). Brunoldi et al ( 26 ) reported that HepG2 cells convert 15-d-PGJ 2 to a GSH conjugate in which the carbonyl on the prostane ring is reduced to a hydroxyl, and the GSH portion of the molecule is subsequently hydrolyzed to a cysteine conjugate.…”
mentioning
confidence: 99%
See 1 more Smart Citation